Efektivitas Sistem Penjaminan Mutu Pendidikan (SPMP) Dalam Menghadapi Kesenjangan Kualitas Pendidikan Antarwilayah - Annuri Putri Dupa; Santi Novita Sari; Harliawan Harliawan; Mohammad Muspawi; Eva Iryani (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The quality of education is a key indicator of human resource development and national competitiveness. However, the disparity in education quality between regions remains a significant challenge in Indonesia, influenced by differences in resources, infrastructure, and institutional capacity. The Education Quality Assurance System (SPMP) serves as a strategic instrument to ensure equitable compliance with National Education Standards through internal (SPMI) and external (SPME) mechanisms. This article aims to analyze the effectiveness of SPMP in addressing the disparity in education quality between regions by reviewing aspects of quality culture, leadership, data utilization, and a contextual approach. The study employed a literature review method, reviewing various relevant scientific sources. The results indicate that SPMP has significant potential to improve education quality through a continuous improvement cycle and the use of evidence-based data. However, its implementation still faces challenges such as limited resources, the digital divide, the risk of bureaucratization, and the low internalization of a quality culture. Therefore, strengthening collaboration, increasing human resource capacity, and policy flexibility based on local contexts are needed so that SPMP can function optimally in realizing equitable education quality.